The psychological impact of the unpredictability of multiple sclerosis: a qualitative literature meta-synthesis - Rose, Hannah; das Nair, Roshan (Mark Allen Healthcare, 2013)
Background: Multiple sclerosis (MS) is a neurological conditioncharacterised by an unpredictable nature. This characteristic is reported to be the largest challenge for individuals with the condition. Chronic illness literature highlights the psychological impact of unpredictability, but there is a paucity of research examining this concept in MS.